P-OGC78 One year experience of a newly established super green ERAS pathway for performing oesophago-gastric cancer resections during the Covid-19 pandemic. (16th December 2021) - Sahni, Dhruv; Khan, Khurram; Gall, Lewis; Kosk, Paulina; Forshaw, Matthew; Macdonald, Andrew; Craig, Carol; MacKay, Colin
Abstract: Background: Surgical oncology services in the UK have been impacted by the COVID-19 pandemic. Various strategies have been employed in an attempt to continue cancer resectional surgery during the pandemic. This study examined our institution's experience and outcomes with a newly established Super Green ERAS pathway for oesophago-gastric (OG) cancer resections during the pandemic. Methods: A retrospective cohort study of consecutive patients who had a resection for OG cancer performed over a 12-month period beginning from the date of the first UK National Lockdown of 23 March 2020. Barring two intervals each lasting 3 weeks, urgent elective cancer surgery continued on our mixed hot and cold site through the establishment of a Super Green ERAS pathway. Patients were confirmed COVID-19 negative within 72 hours pre-admission and retested 72-hourly post-op. 14 days self-isolation pre-admission was mandated. Patients not complying had their surgery postponed. Transhiatal oesophagectomy was the preferred approach for oesophagectomy during the pandemic. Results: 45 resections (33 oesophagectomies, 10 gastrectomies and 2 trial of dissections) were performed. 37 (82.2%) patients were male with a median age of 64 (IQR 58-71) years. 3 patients were postponed due to non-adherence with self-isolation. No patients tested positive for COVID-19 post-operatively, hence, there was no COVID-19-related morbidity. Nine patients developed pneumonia. Seven patients had an anastomotic leak, all of whom were successfully rescued. One patient required a clamshell thoracotomy due to intra-operative mediastinal bleeding followed by a return to theatre for reconstruction 48hrs later. Median length of stay was 12 (IQR 9-18) days. There was no in-hospital mortality. Conclusions: OG cancer resections can be performed safely despite COVID-19, with favorable clinical outcomes when a Super Green ERAS pathway is strictly adhered to. Implementation of such pathways will enable surgical oncology services, including OG cancer resections, to continue to ensure best possible outcomes for cancer patients despite any future waves of the COVID-19 pandemic.